The SCN9A channel and plasma membrane depolarization promote cellular senescence through Rb pathway. Issue 3 (15th February 2018) - Warnier, Marine; Flaman, Jean‐Michel; Chouabe, Christophe; Wiel, Clotilde; Gras, Baptiste; Griveau, Audrey; Blanc, Elena; Foy, Jean‐Philippe; Mathot, Pauline; Saintigny, Pierre; Van Coppenolle, Fabien; Vindrieux, David; et al.
Summary: Oncogenic signals lead to premature senescence in normal human cells causing a proliferation arrest and the elimination of these defective cells by immune cells. Oncogene‐induced senescence (OIS) prevents aberrant cell division and tumor initiation. In order to identify new regulators of OIS, we performed a loss‐of‐function genetic screen and identified that the loss of SCN9A allowed cells to escape from OIS. The expression of this sodium channel increased in senescent cells during OIS. This upregulation was mediated by NF‐κB transcription factors, which are well‐known regulators of senescence. Importantly, the induction of SCN9A by an oncogenic signal or by p53 activation led to plasma membrane depolarization, which in turn, was able to induce premature senescence. Computational and experimental analyses revealed that SCN9A and plasma membrane depolarization mediated the repression of mitotic genes through a calcium/Rb/E2F pathway to promote senescence. Taken together, our work delineates a new pathway, which involves the NF‐κB transcription factor, SCN9A expression, plasma membrane depolarization, increased calcium, the Rb/E2F pathway and mitotic gene repression in the regulation of senescence. This work thus provides new insight into the involvement of ion channels and plasma membrane potential in the control of senescence.